2010
DOI: 10.1186/1472-6963-10-285
|View full text |Cite
|
Sign up to set email alerts
|

Access to and utilisation of GP services among Burmese migrants in London: a cross-sectional descriptive study

Abstract: BackgroundAn estimated 10,000 Burmese migrants are currently living in London. No studies have been conducted on their access to health services. Furthermore, most studies on migrants in the United Kingdom (UK) have been conducted at the point of service provision, carrying the risk of selection bias. Our cross-sectional study explored access to and utilisation of General Practice (GP) services by Burmese migrants residing in London.MethodsWe used a mixed-method approach: a quantitative survey using self-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 14 publications
3
19
1
3
Order By: Relevance
“…29,32,41,62 Results were consistent with studies by Mladovsky and others that migrants are confused about host country health systems and entitlements. 29,40,62 Several issues warrant improvement, including accessibility, communication, and clarity on migrant entitlements and GP responsibilities.…”
Section: Nhs Principlessupporting
confidence: 85%
See 1 more Smart Citation
“…29,32,41,62 Results were consistent with studies by Mladovsky and others that migrants are confused about host country health systems and entitlements. 29,40,62 Several issues warrant improvement, including accessibility, communication, and clarity on migrant entitlements and GP responsibilities.…”
Section: Nhs Principlessupporting
confidence: 85%
“…28 Access includes receipt of healthcare and consideration of the process and quality of care received. 29 It is affected by both intrinsic (eg, socio-cultural beliefs, 29 language, 13 literacy [30][31][32] ) and extrinsic factors (eg, service quality, service location 29,33 ). Equitable access requires information that is relevant, timely, and useful, and an enabling environment that treats service-users with respect and dignity.…”
Section: Introductionmentioning
confidence: 99%
“…Our search yielded three publications specifically concerned with monitoring migrant health in Europe [9][10][11], several research papers investigating the situation in selected EU countries [12][13][14][15][16], a number of outputs from recent EU-funded projects [17][18][19][20][21], several reports from international organizations related to migration and health [1][2][3][22][23][24][25], and a number of relevant documents from the EU and the Council of Europe [4][5][6][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Some years earlier, a study by Steen & Hunskår (2004) showed that 84% of patients could name their assigned GP. A high GP registration rate and a low rate of utilizing GP services have also been found (Aung et al, 2010).…”
Section: How Do Immigrants Access and Use The Gp Scheme?mentioning
confidence: 98%
“…Norwegian studies show that immigrants have a higher use of GPs than Norwegianborn individuals Aung et al, 2010); this provides a possible justification including unclear symptoms and poor communication leading to repeated visits. Also local EWs register higher utilization rates among migrants compared to Norwegian-born patients while Hargreaves et al (2006) showed in their study a lower utilization level among immigrants living in London.…”
Section: Equity and Equality In Health Carementioning
confidence: 99%